Short and long term outcomes and associated factors in a cohort of preterm babies born at a tertiary care centre in Sri Lanka - Sasrubi, S. (University of Jaffna, 2021)
Preterm birth, defined as childbirth occurring at or less than 37 completed weeks or 259 days of gestation and is a major determinant of neonatal mortality and morbidity. An institutional based cohort study was carried out to determine the short and long-term outcomes and associated factors among cohort preterm babies born in Teaching Hospital, Jaffna between October 2015 and February 2017. Anthropometric measurements, neuro-developmental scores using Bayley-III, and behavioral patterns at the end 3, 6, 12, and 18 months of age of 167 preterm babies of their corrected age prematurity were obtained, excluding 5 babies who died during follow-up. The results were analyzed using SPSS version 16.0, chi-square test, paired t-test, one-way ANOVA test, logistic regression, trend analysis, and Kaplan-Meier survival.Following maternal factors were identified as risk for very preterm delivery; aged teens (OR:1.895), Hinduism (OR:1.447), living in the nuclear family (OR:1.274), primi (OR:3.021), maintained pregnancy interval of <1 year (OR:1.117), had sexual intercourse before two weeks of delivery (OR:1.607) and diagnosed with pregnancy complications (OR:1.695). The majority of the preterm babies were males (54.3%). The mean birth weight, body length, and head circumference of the preterm babies were 2.2 (±0.6) kg, 46.3 (±4.8) cm, and 32.0 .(±3.3) cm respectively. Catch-up weight was reached by moderate to late preterm babies at 18 months, while body length was in risk status. But very preterm babies reached catch-up in body weight and length at 6 months and maintained in the normal range. The following factors were identified as risk for delay in both body weight and length catch-up; the babies who were born with low birth weight, (OR:1.420), admitted to neonatal intensive care unit (OR:l.627), and re-hospitalized (OR:1.231). The following factors were identified as risk for neuro-developemental delay; children of employed mothers (OR:1.354), born at very preterm (OR:1.460), treated for short-term complications (OR:2.337), admitted to neonatal intensive care unit (OR:2.653), stayed at the hospital for more than 2 weeks (OR:1.317), discharged from hospital with complications related to prematurity (OR:2.857), re-hospitalized (OR:7.664). The behavioral problem, i.e. inattention was recorded in four children.
Keywords: Preterm babies; Short term outcome; Growth pattern; Neuro-development behavioural pattern